Modern Full-Stack Web Development with ASP.NET Core a project-based guide to building web applications with ASP.NET Core 9 and JavaScript frameworks - Malavasi, Alexandre (2025)
Master APIs, authentication, cloud deployment, and DevOps processes to create full-stack web apps with ASP.NET Core, Blazor, React, Angular, and Vue Key Features Integrate Angular, Vue.js, and React frameworks into ASP.NET Core projects following frontend development best practices Use ASP.NET Core to its full potential to create a versatile backend layer based on RESTful APIs Secure your application against threats and vulnerabilities in a time-efficient way Purchase of the print or Kindle book includes a free PDF eBook Book Description In the ASP.NET Core ecosystem, choosing the right JavaScript framework is key to addressing diverse project requirements. Witten by a four-time Microsoft MVP with 16 years of software development experience, this book is your comprehensive guide to mastering full-stack development, combining ASP.NET Core's robust backend capabilities with the dynamic frontend power of Vue.js, Angular, and React. This book uses ASP.NET Core to teach you best practices for integrating modern JavaScript frameworks, and creating responsive, high-performance applications that deliver seamless client-server interactions and scalable RESTful APIs. In addition to building expertise in ASP.NET Core's core strengths, such as API security, architecture principles, and performance optimization, the chapters will help you develop the essential frontend skills needed for full-stack development. Sections on Blazor take a C#-based approach to creating interactive UIs, showcasing ASP.NET Core's flexibility in handling both server and client-side needs. By the end of this book, you will have a complete toolkit for designing, deploying, and maintaining complex full-stack applications, along with practical knowledge of both backend and frontend development. What you will learn Explore ASP.NET Core basics, including its architecture, components, and differences from previous versions Understand advanced topics like dependency injection, middleware, configuration, and logging in depth Develop complex server-side web applications using ASP.NET Core Grasp the basics of Blazor and see how it enables you to build interactive web UIs using C# Create simple client-side applications using Blazor WebAssembly Integrate JavaScript frameworks with ASP.NET Core for full-stack web development Who this book is for This book is for beginners in web development and anyone looking to build a strong foundation in ASP.NET Core, as well as gain essential knowledge of JavaScript frameworks like Angular, React, and Vue.js. Whether you're new to web development or have some experience, this book offers a project-based, hands-on approach to mastering ASP.NET Core as the backbone of full-stack applications. Alongside ASP.NET Core, you'll develop basic skills in modern JavaScript frameworks and learn to integrate them effectively to build dynamic, robust web applications from the ground up.
Print Version Record
Keywords: Active server pages; Microsoft .NET Framework; Web site development; Application software -- Development; C (Computer program language); Sites Web; Développement; Logiciels d'application; Développement; C (Langage de programmation); ASP.NET; C#; Programming Languages; COMPUTERS; Web